Summer Grazing of Steers in Western Kansas - Dumler, Troy J.; O'Brien, Daniel M.; Jones, Rodney (My University, 2008)
This publication is a guide to budget estimate costs and returns for a season-long and an early-intensive grazing system in Western, KS.
MF1007_2008-10
Keywords: MF1007; Economics; Livestock; MF